New species of Euplocania Enderlein (Psocodea: ‘Psocoptera’: Psocomorpha) from Colombia and Ecuador - Vinasco-Mondragón, Andrés Felipe; González-Obando, Ranulfo; Aldrete, Alfonso N. García (Zootaxa, 2022)
Four species of Euplocania from Colombia (Euplocania huitota n. sp., E. kakwa n. sp., E. nukak n. sp. and E. ticuna n. sp.) and four species from Ecuador (E. napensis n. sp., E. shuar n. sp., E. teslai n. sp. and E. waorani n. sp.), in four species groups, are described and illustrated. The new species group ticuna, from Colombia and waorani, from Ecuador are diagnosed. The number of species in Euplocania is raised to 61, in 17 species groups. A key to the males of the known species of Euplocania is presented.